Design and implementation of hollow cilium cylinder MEMS vector hydrophone. (15th January 2021) - Yang, Xi; Xu, Qingda; Zhang, Guojun; Zhang, Lansheng; Wang, Weidong; Shang, Zhenzhen; Shi, Yiming; Li, Chenge; Wang, Renxin; Zhang, Wendong
Highlights: Design of a novel MEMS vector hydrophone based on fish bionics. The hollow cilium cylinder vector hydrophone has a simple fabrication. The feasibility of the hydrophone is proved with theory and experiment. The hydrophone has the high sensitivity and wide working bandwidth. Abstract: The cilium MEMS vector hydrophone (CVH) plays an important role in detecting underwater acoustic targets, but there are still problems of low sensitivity and insufficient working bandwidth. In this paper, hollow cilium cylinder vector hydrophone (HCVH) is presented, which can improve sensitivity and working bandwidth within a certain range. Acting as the received acoustic signal structure, a hollow cylinder can not only ensure that sensitivity is improved by increasing the size of area which receives sound, but also reduce its weight to improve the stability of hydrophone. Through the theoretical analysis and the simulation, the relationship between the structure parameters and working performance of the hydrophone is obtained, and the specific size of the sensitive structure is determined. The experimental results show that the sensitivity of HCVH is increased by 8.7 dB in 20–1000 Hz, reaching up to −185.6 dB (re 1 V/µPa) at 1250 Hz. In addition, HCVH has a good directivity.